Analysis of Regional Government Financial Performance and Its Impact on Poverty in South Sumatra - apriyadi, apriyadi; Alfitri, Alfitri; Sriati, Sriati; Thamrin , Husni (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
This study aims to analyze the financial performance of local governments in the districts and cities of South Sumatra Province and its impact on poverty levels. The data used were obtained from the Ministry of Finance and the Central Bureau of Statistics, covering regional revenue and expenditure budget data as well as poverty figures for the period 2019–2022. This research employs a panel data analysis method, which combines cross-sectional and time-series data to gain a deeper understanding of the dynamics of the subject under study. The findings indicate that the majority of districts and cities experienced a decrease in poverty levels, except South Ogan Komering Ulu Regency. An F-statistic of 1.747 and a p-value of 1.264 > 0.05 show that, according to the fixed effect model's overall estimation, financial performance does not significantly affect the poverty rate. The overall R square result demonstrates that the independent variables can account for 14.63% of the variation in poverty figures. Among the six ratios, only the effectiveness ratio had a positive and significant impact, with a regression coefficient of.3426081 and a p-value of 0.019 < 0.05. Overall, local governments' financial performance does not entirely determine the dynamics of poverty in South Sumatra Province. This underscores the need to consider other factors in reducing poverty rates. Although the effectiveness ratio has a positive impact, other unexplored variables play a dominant role. Therefore, as a recommendation, local governments need to broaden their focus from merely improving financial performance to other aspects affecting poverty.